2002
DOI: 10.1023/a:1013886130805
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It was the purpose of this investigation to prove the biomechanical properties, the osteoconductive capacity and the degradation rate of alpha tricalcium phosphate (alpha TCP), a neutralized glass ceramics (GB9N) and a composite material (GB9N+copolymers). In a weight-bearing animal model six substitutes each were implanted in the medial tibial head of the right lower leg of adult Merino-sheep in a standardized surgical technique. After nine months the implants were harvested and prepared for histomorphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A sufficient number of studies have shown that the sheep has a weight-bone ratio similar to that of humans. The bone structure as well as the immune, blood and lymphatic systems of sheep are largely homologous to those of humans [ 55 , 56 , 57 , 58 ]. This leads to our third step, the test in a critical size defect in sheep femoral condyle.…”
Section: Discussionmentioning
confidence: 99%
“…A sufficient number of studies have shown that the sheep has a weight-bone ratio similar to that of humans. The bone structure as well as the immune, blood and lymphatic systems of sheep are largely homologous to those of humans [ 55 , 56 , 57 , 58 ]. This leads to our third step, the test in a critical size defect in sheep femoral condyle.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D porous structure provides space for new bone formation, the support necessary for cells to proliferate and maintain their differential function, mimics many roles of the extracellular matrix, and its architecture defines the ultimate shape of new bone [5, 6]. …”
Section: Introductionmentioning
confidence: 99%